Paciente masculino de 54 años de edad con cáncer colorrectal y desnutrición moderada. - Félix Mendoza, Nicole Maite (2021)
The present case is about a 54-year-old male patient with colorectal cancer and moderate malnutrition who attended a medical consultation with abdominal pain, bloating, nausea and weight loss, reflected in loss of muscle mass and fat mass. A comprehensive care process was carried out with the aim of improving the nutritional status of the patient. The anthropometric, biochemical, clinical and dietary method was carried out, resulting in a nutritional diagnosis of Low weight (NC-3.1), Deficient protein-energy intake (NI-5.3), related to abdominal pain, weight loss and nausea product. of colorectal cancer and moderate malnutrition. In addition, a food plan was established based on the nutritional needs of the patient, so a soft intestinal diet was prescribed at the beginning of the follow-up and another hyper protein diet that was progressively adapted. As a result, it was possible to improve the nutritional status of the patient with colorectal cancer and moderate malnutrition with a one-month follow-up and monitoring, for which benefits were obtained for the patient, reflected in their body weight, muscle mass, fat mass, biochemical values and clinical manifestations.